EVIDENCE meta-analysis: evaluating minimal residual disease as an intermediate clinical end point for multiple myeloma - Landgren, Ola; Prior, Thomas J.; Masterson, Tara; Heuck, Christoph; Bueno, Orlando F.; Dash, Ajeeta B.; Einsele, Hermann; Goldschmidt, Hartmut; Knop, Stefan; Li, Cong; Mellqvist, Ulf-Henrik; McFadden, Ian; et al. (Blood, 2024)
Estimating progression-free survival (PFS) and overall survival superiority during clinical trials of multiple myeloma (MM) has become increasingly challenging as novel therapeutics have improved patient outcomes. Thus, it is imperative to identify earlier end point surrogates that are predictive of long-term clinical benefit. Minimal residual disease (MRD)-negativity is a common intermediate end point that has shown prognostic value for clinical benefit in MM. This meta-analysis was based on the US Food and Drug Administration guidance for considerations for a meta-analysis of MRD as a clinical end point and evaluates MRD-negativity as an early end point reasonably likely to predict long-term clinical benefit. Eligible studies were phase 2 or 3 randomized controlled clinical trials measuring MRD-negativity as an end point in patients with MM, with follow-up of ≥6 months following an a priori-defined time point of 12 ± 3 months after randomization. Eight newly diagnosed MM studies evaluating 4907 patients were included. Trial-level associations between MRD-negativity and PFS were R2WLSiv, 0.67 (95% confidence interval [CI], 0.43-0.91) and R2copula 0.84 (0.64 to >0.99) at the 12-month time point. The individual-level association between 12-month MRD-negativity and PFS resulted in a global odds ratio (OR) of 4.02 (95% CI, 2.57-5.46). For relapse/refractory MM, there were 4 studies included, and the individual-level association between 12-month MRD-negativity and PFS resulted in a global OR of 7.67 (4.24-11.10). A clinical trial demonstrating a treatment effect on MRD is reasonably likely to eventually demonstrate a treatment effect on PFS, suggesting that MRD may be an early clinical end point reasonably likely to predict clinical benefit in MM, that may be used to support accelerated approval and thereby, expedite the availability of new drugs to patients with MM.
Online veröffentlicht: 20. Mai 2024
Gesehen am 06.10.2025